2006
DOI: 10.1101/lm.317806
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic neurons mediate CaMKII-dependent enhancement of courtship suppression

Abstract: In Drosophila, calcium/calmodulin-dependent protein kinase II (CaMKII) activity is crucial in associative courtship conditioning for both memory formation and suppression of courtship during training with a mated female. We have previously shown that increasing levels of constitutively active CaMKII, but not calcium-dependent CaMKII, in a subset of neurons can decrease the initial level of courtship and enhance the rate of suppression of courtship in response to a mated female. In this study, we demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
1
22
0
2
Order By: Relevance
“…To test this, we used Brp-Short to examine synapse number in GABAergic inhibitory neurons projecting to the antennal lobe using the GAD1-GAL4 driver (Ng et al, 2002). Though GAD1-positive neurons project throughout the antennal lobe (Mehren and Griffith, 2006), we restricted our analyses to the DA1 glomerulus, where we observed reductions in excitatory synapses (Figure 2—figure supplements 3–4) following LRP4 disruption. When LRP4 function was impaired using the lrp4 dalek mutant or RNAi in these neurons, synapse number was unaffected (Figure 4A–B,D).…”
Section: Resultsmentioning
confidence: 99%
“…To test this, we used Brp-Short to examine synapse number in GABAergic inhibitory neurons projecting to the antennal lobe using the GAD1-GAL4 driver (Ng et al, 2002). Though GAD1-positive neurons project throughout the antennal lobe (Mehren and Griffith, 2006), we restricted our analyses to the DA1 glomerulus, where we observed reductions in excitatory synapses (Figure 2—figure supplements 3–4) following LRP4 disruption. When LRP4 function was impaired using the lrp4 dalek mutant or RNAi in these neurons, synapse number was unaffected (Figure 4A–B,D).…”
Section: Resultsmentioning
confidence: 99%
“…In courtship conditioning in fruit-flies, constitutively activated CaMKII in cholinergic neurons of the antennal lobe plays roles in behavioral change during training [16], [43], and CaMKII in neurons of the lateral protocerebrum or the central complex plays roles in acquisition of memory [15]. In olfactory learning in fruit-flies, it has been reported that CREB-dependent transcription and translation of CaMKII proteins in Kenyon cells of the mushroom body [19], [20] or dorsal-anterior-lateral (DAL) neurons [44] are necessary for LTM formation.…”
Section: Discussionmentioning
confidence: 99%
“…Gad1-Gal4 (line 2B) was constructed by Toshi Kitamoto using a Gad1 promoter fragment and was first published in ref. 26 , where it was called “ Gad2B-Gal4 ”. Gr28b MB03888 was reported in ref.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore targeted our electrodes to this cluster when we used a Gad1-Gal4 line 26 to drive CD8::GFP expression in putative GABAergic neurons. In order to determine if the CD8::GFP-expressing somata in this cluster are indeed GABAergic, we performed dual immunofluorescence confocal microscopy with anti-CD8 and anti-GABA antibodies.…”
Section: Extended Datamentioning
confidence: 99%